2013
DOI: 10.1007/s11096-013-9875-8
|View full text |Cite
|
Sign up to set email alerts
|

Medication reconciliation by a pharmacy technician in a mental health assessment unit

Abstract: Medication discrepancies are common within mental health services with potentially significant consequences for patients.Trained pharmacy technicians are able to reduce the frequency of discrepancies, improving safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 20 publications
1
58
0
Order By: Relevance
“…10 In the UK, MR is 44 described similarly and recommended to be performed every time a transfer of care takes 45 place. 11 …”
mentioning
confidence: 99%
“…10 In the UK, MR is 44 described similarly and recommended to be performed every time a transfer of care takes 45 place. 11 …”
mentioning
confidence: 99%
“…When asked about the medications that they are taking, most patients think in terms of prescriptions they receive at a pharmacy, but they may not report receiving long-acting injectable antipsychotic medications, oral or long-acting injectable contraceptives, or nonprescribed medications (e.g., over-the-counter medications, vitamins, herbal products, nutritional supplements) unless specifically asked. Approaches that have been employed to develop an accurate medication list include using a structured format for the medication history (Drenth-van Maanen et al 2011) or involving hospital-based clinical pharmacists or pharmacy technicians in taking a medication history (Brownlie et al 2014;Kwan et al 2013). With the use of electronic prescribing and electronic health records, information on patients' previous medications will be increasingly available to clinicians.…”
Section: Methodsmentioning
confidence: 99%
“…5 However, a study conducted in the United Kingdom observed that medication errors are common in mental health services, and that 56.2% of the errors occurred in patients hospitalized in wards, during three months of hospitalization. 6 Another study of medication errors in a Japanese psychiatric hospital found a 2.14 rate of medication errors reported for every 1,000 patients per day, which suggests the underreporting of medication errors in the studied context. 7 The focus of assistance should therefore be on strategies that prevent errors at different stages of the medication system and ensure patient safety.…”
Section: Introductionmentioning
confidence: 94%